2010
DOI: 10.1159/000258708
|View full text |Cite
|
Sign up to set email alerts
|

Intrathymic T Cell Migration Is a Multivectorial Process under a Complex Neuroendocrine Control

Abstract: The thymus is responsible for normal T cell development, a process that includes cell proliferation, death, migration, and T cell receptor gene rearrangements. Moreover, it depends on interactions between developing thymocytes and thymic microenvironmental cells. Along with differentiation, thymocytes migrate and such oriented movement is regulated by several molecular interactions, comprising extracellular matrix (ECM) elements and chemokines. We postulated that intrathymic T cell migration is a multivectoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
0
13
0
3
Order By: Relevance
“…The infection of B6 mice by T. cruzi leads to increased levels of miR-10a in thymic epithelial cells (TEC) involved in intrathymic T cell differentiation, which can be caused by TGF-β signaling and impact thymus atrophy during infection [124,125].…”
Section: Trypanosoma-host Interactionsmentioning
confidence: 99%
“…The infection of B6 mice by T. cruzi leads to increased levels of miR-10a in thymic epithelial cells (TEC) involved in intrathymic T cell differentiation, which can be caused by TGF-β signaling and impact thymus atrophy during infection [124,125].…”
Section: Trypanosoma-host Interactionsmentioning
confidence: 99%
“…Importantly, hormones can control thymus physiology, including T-cell development, and the thymus itself can also affect endocrine axes. 1 Investigations in the 1970s and 1980s showed that neonatal thymectomy generated abnormal development of secondary sexual organs, 2 and that a given cell-mediated antigen stimulation triggered a feedback response involving the production of glucocorticoids and IL-1. 3 During the 1980s, the existence of a common syntax in neuroendocrine and lymphoid tissues was also proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The thymus is the primary lymphoid organ where bone marrow-derived T cells precursors differentiate and proliferate, ultimately leading to migration of positively selected thymocytes to the peripheral organs where they respond to antigen stimulation and undergo effector differentiation (1,2). It has been well defined that the thymus provides an optimal and essential microenvironment for T cell development and maturation (3).…”
Section: Introductionmentioning
confidence: 99%